Allosteric Modulators of the CB(1) Cannabinoid Receptor: A Structural Update Review - Morales, Paula (Cannabis Cannabinoid Res, 2016)
In 2005, the first evidence of an allosteric binding site at the CB(1)R was provided by the identification of three indoles of the company Organon that were allosteric enhancers of agonist binding affinity and, functionally, allosteric inhibitors of agonist activity. Since then, structure–activity relationships of indoles as CB(1)R modulators have been reported. Targeting the allosteric site on CB(1)R, new families structurally based on urea and on 3-phenyltropane analogs of cocaine have been discovered as CB(1)R-negative allosteric modulators (NAMs), respectively, by Prosidion and by the Research Triangle Park. Endogenous allosteric ligands of different nature have been identified more recently. Thus, the therapeutic neuroprotection application of lipoxin A4, an arachidonic acid derivative, as an allosteric enhancer of CB(1)R activity has been confirmed in vivo. It was also the case of the steroid hormone, pregnenolone, whose negative allosteric effects on Δ(9)-tetrahydrocannabinol (Δ(9)-THC) were reproduced in vivo in a behavioral tetrad model and in food intake and memory impairment assays. Curiously, the peroxisome proliferator-activated receptor-γ agonist fenofibrate or polypeptides such as pepcan-12 have been shown to act on the endocannabinoid system through CB(1)R allosteric modulation. The mechanistic bases of the effects of the phytocannabinoid cannabidiol (CBD) are still not fully explained. However, there is evidence that CBD behaves as an NAM of Δ(9)-THC- and 2-AG. Allosteric modulation at CB(1)R offers new opportunities for therapeutic applications. Therefore, further understanding of the chemical features required for allosteric modulation as well as their orthosteric probe dependence may broaden novel approaches for fine-tuning the signaling pathways of the CB(1)R.